2021
DOI: 10.1097/mao.0000000000003210
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Deep Learning Model for Automated Diagnosis of Otoscopic Images

Abstract: Objectives: To develop a multiclass-classifier deep learning model and website for distinguishing tympanic membrane (TM) pathologies based on otoscopic images. Methods: An otoscopic image database developed by utilizing publicly available online images and open databases was assessed by convolutional neural network (CNN) models including ResNet-50, Inception-V3, Inception-Resnet-V2, and MobileNetV2. Training and testing were conducted with a 75:25 breakdown. Area under the curve of receiver operating character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…AI algorithms achieved a pooled accuracy of 90.7% (95%CI: 90.1-91.3%) to difference between normal or abnormal otoscopy images with substantial heterogeneity between studies (n = 14 studies, I 2 = 96.9%, p = .001, Figure 3). Four studies [14][15][16][17] used the Özel Van Akdamar Hospital otoscopic image database to train binary algorithms using various classification techniques. Simon et al 14 demonstrated that pretrained convolutional neural networks (CNNs) and support vector machines (SVMs) could achieve greater classification accuracy than k-nearest neighbours (k-NNs), artificial neural networks (ANNs), decision trees (DTs) or the Naïve Bayes technique.…”
Section: Normal Versus Abnormalmentioning
confidence: 99%
See 1 more Smart Citation
“…AI algorithms achieved a pooled accuracy of 90.7% (95%CI: 90.1-91.3%) to difference between normal or abnormal otoscopy images with substantial heterogeneity between studies (n = 14 studies, I 2 = 96.9%, p = .001, Figure 3). Four studies [14][15][16][17] used the Özel Van Akdamar Hospital otoscopic image database to train binary algorithms using various classification techniques. Simon et al 14 demonstrated that pretrained convolutional neural networks (CNNs) and support vector machines (SVMs) could achieve greater classification accuracy than k-nearest neighbours (k-NNs), artificial neural networks (ANNs), decision trees (DTs) or the Naïve Bayes technique.…”
Section: Normal Versus Abnormalmentioning
confidence: 99%
“…Four studies [14][15][16][17] used the Özel Van Akdamar Hospital otoscopic image database to train binary algorithms using various classification techniques. Simon et al 14 demonstrated that pretrained convolutional neural networks (CNNs) and support vector machines (SVMs) could achieve greater classification accuracy than k-nearest neighbours (k-NNs), artificial neural networks (ANNs), decision trees (DTs) or the Naïve Bayes technique.…”
Section: Normal Versus Abnormalmentioning
confidence: 99%
“…In [121], an ear infection classifier 62 was implemented and trained with published otoscopic images, from which transfer learning on MobileNetV2 was found to outperform Inception-V3, ResNet-50, and InceptionResnet-V2. In [57], the viability of Google's Teachable Machine was assessed against the diagnosis of tooth-marked tongue, a condition in which tooth traces develop on the tongue.…”
Section: Healthcare Diagnosismentioning
confidence: 99%
“…There is a growing increase in the number of web-based implementations of deep learning frameworks that provide convenient public access and ease of implementation [1][2][3][4][5][6]. Notably, many web servers have been developed for sequence design tasks, like analysis of RNA, DNA, or proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[3] There is a growing increase in the number of web-based implementations of deep learning frameworks that provide convenient public access and ease of use. [4][5][6][7][8][9] Notably, many web servers have been developed for sequence design tasks, like analysis of RNA, DNA, or proteins. For example, survival analysis based on mRNA data (GENT2, [10] PROGgeneV2, [11] SurvExpress, [12] MEXPRESS, [13] etc.…”
Section: Introductionmentioning
confidence: 99%